2020
DOI: 10.1177/0748233720936835
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide nanoparticle genotoxicity: A review of recent in vivo and in vitro studies

Abstract: Titanium dioxide nanoparticles (TiO2 NPs, size <100 nm) find applications in a wide range of products including food and cosmetics. Studies have found that exposure to TiO2 NPs can cause inflammation, cytotoxicity, genotoxicity and cell apoptosis. In this article, we have reviewed the recent literature on the potential of TiO2 NPs to cause genotoxicity and summarized the results of two standard genotoxicity assays, the comet and micronucleus (MN) assays. Analysis of these peer-reviewed publications shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 86 publications
0
24
0
Order By: Relevance
“…In addition to the mechanisms underlying ROS generation, it also remains unknown as to how the TiO 2 NPs interact with the TiO 2 NTs and how this interaction regulates the intracellular ROS levels. Nano-TiO 2 can cause genotoxicity [ 41 ]. Furthermore, the ROS-mediated stress within cells could be the main mechanism for the genotoxicity of nano-TiO 2 [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the mechanisms underlying ROS generation, it also remains unknown as to how the TiO 2 NPs interact with the TiO 2 NTs and how this interaction regulates the intracellular ROS levels. Nano-TiO 2 can cause genotoxicity [ 41 ]. Furthermore, the ROS-mediated stress within cells could be the main mechanism for the genotoxicity of nano-TiO 2 [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…TiO 2 is the most widely used nanomaterial worldwide, employed in a variety of applications ranging from medical devices to products used in everyday life [31,34]. The present work was carried out using TiO 2 NP as nanomaterial model since their genotoxicity has been extensively studied and they are known to induce MN in a variety of cell lines [12,[35][36][37][38]. Moreover, following OECD TG 487 and OECD report No.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, results observed in these experiments indicate that the two treatment options recommended for testing nanomaterials by the CBMN assay are not good options in this particular case, since they resulted similar than the standard cotreatment, and the data obtained substantially differed from those coming from FCMN test in the absence of Cyt-B. Following the recommendations provided by OECD WPMN [22], a number of researchers evaluated MN induction by TiO 2 NP exposure applying either post-treatment [12,[70][71][72] or delayed co-treatment [51,55,73,74] in a number of different cell types. Similar to our results, these studies frequently found increases in MN frequency after TiO 2 NP exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, exposure of human beings to TiO 2 materials is plausible. Although Ti has been considered as biologically inert element, it has still been suggested that exposure to TiO 2 NMs may induce adverse health effects, for instance, genotoxicity, developmental toxicity, vascular toxicity, and neurotoxicity (Cao et al, 2018; Chang et al, 2021; Wani & Shadab, 2020; Wu, Chen, et al, 2020). Indeed, reliable data already revealed that TiO 2 materials were genotoxic, and thus, TiO 2 materials have been classified as possible human carcinogen (Baranowska‐Wójcik et al, 2020; Guseva Canu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%